Implementasi Sistem Informasi Disposisi Surat Digital untuk Meningkatkan Efisiensi Administrasi di DPPKB Nabire - Gunawan Prayitno; Anggreini Wibowo Puspita Sari (STMIK Pesat Nabire, 2025)
Manual handling of incoming letters in government institutions often results in inefficiencies in recording, tracking, and disposition delivery. This study aims to develop a Java-based application for managing incoming letter dispositions to enhance administrative efficiency at the Office of Population Control and Family Planning (DPPKB) of Nabire Regency. The system was developed using the waterfall method, which includes the stages of analysis, design, implementation, testing, and maintenance. The results show a 30% increase in disposition speed and a 50% decrease in recording errors. Furthermore, the application supports real-time letter tracking and role-based user access. The findings indicate that digitizing the letter disposition system can significantly accelerate administrative processes and reinforce the principles of good governance.